Pengaruh Mapping Ignition Timing Engine Control Unit (ECU) Programmable Terhadap Torsi Dan Daya Motor Bensin 4 Langkah - Warso; Prabowo, Nugrah Rekto; Sutarno; Mastur (Universitas Nusa Putra, 2020)
The current technology applied to motorbikes is growing, so that it can improve the performance of fuel injection systems that can be controlled electronically by the Engine Control Unit (ECU) with sensors and actuators. ECU is currently produced by an Indonesian racing company other than a motorcycle manufacturer, the Programmable ECU which can change Ignition Timing (ignition time) with the aim of improving engine performance. That way it is necessary to do research that aims to determine the ignition time in the ECU program for torque and motor power of 4 steps. To simplify the implementation, the results of tables and graphs can be analyzed. The effect of standard ECU ignition time at 5 ° before TDC produces maximum torque of 14.86 Nm at 7500 rpm engine speed and 16.9 maximum power at 8500 rpm engine speed. The engine circulates 7500 rpm mapping ECU 1 torque is increased 3% to 15.25 Nm and power rises 3% to 17.4 HP on the 8750 rpm engine. After mapping again to ECU 2 and a 3% increase in torque and 4% power compared to the use of standard ECU ignition time. The resulting torque ECU maps 2 by 15.29 Nm at 7500 rpm engine speed and produces a maximum power of 17.6 HP on the 8750 rpm engine. At ECU 1, mapping with the highest ignition time at 32 ° before the top dead center is carried out. In mapping ECU 2 uses the ignition point time at 35 ° before the top dead center.